A systematic review to comprehend the cultural representation in L2 Mandarin textbooks - Lin, Wenyue; Ang, Lay Hoon; Chan, Mei Yuit; Paramasivam, Shamala (Universiti Putra Malaysia, 2021)
Cultural representation in foreign/second language textbooks has received considerable research attention in recent years. This diachronic study reviews previous studies’ methodological trends and research foci on cultural representation in L2 Mandarin textbooks from 2005–2020. It systematically searched all relevant publications in three accessible databases: Web of Science, Scopus, and CNKI. A total number of 48 relevant publications were collected and analyzed. The review indicates that most publications are empirical studies, covering qualitative, quantitative, and mixed studies and most sampled textbooks are elementary textbooks from China. It also reveals that the main source for collecting data is documented, and the commonly used data analysis methods are comparative, content, discourse, and semiotic analysis. Besides that, examining cultural elements in textbooks seems to be a key research focus among the publications, followed by analyzing cultural orientation, unconventional culture phenomenon, and ideology behind cultural representation in textbooks. The current study contributes to the literature by providing a detailed review of cultural representation in L2 Mandarin textbooks and identifying the research gaps. Accordingly, it concludes with recommendations for future research to study cultural representation in textbooks.